Biosynthesis and Ether‐Bridge Formation in Nargenicin Macrolides. (11th February 2019) - Pidot, Sacha J.; Herisse, Marion; Sharkey, Liam; Atkin, Liselle; Porter, Jessica L.; Seemann, Torsten; Howden, Benjamin P.; Rizzacasa, Mark A.; Stinear, Timothy P.
Abstract: The nargenicin family of antibiotics are macrolides containing a rare ether‐bridged cis ‐decalin motif. Several of these compounds are highly active against multi‐drug resistant organisms. Despite the identification of the first members of this family almost 40 years ago, the genetic basis for the production of these molecules and the enzyme responsible for formation of the oxa bridge, remain unknown. Here, the 85 kb nargenicin biosynthetic gene cluster was identified from a human pathogenic Nocardia arthritidis isolate and this locus is solely responsible for nargenicin production. Further investigation of this locus revealed a putative iron‐α‐ketoglutarate‐dependent dioxygenase, which was found to be responsible for the formation of the ether bridge from the newly identified deoxygenated precursor, 8, 13‐deoxynargenicin. Uncovering the nargenicin biosynthetic locus provides a molecular basis for the rational bioengineering of these interesting antibiotic macrolides. Abstract : Bau von (Oxa‐)Brücken : Der biosynthetische Locus für das potente Antibiotikum Narbenicin wurde aus einem humanpathogenen Nocardia ‐Stamm identifiziert. Geninaktivierungsstudien identifizierten eine ungewöhnliche Dioxygenase, die für die Bildung von Etherbrücken verantwortlich ist. Bei Entfernung der Etherbrücke verschwindet die antibiotische Aktivität von Nargenicin.